Climate services and insurance: scaling climate smart agriculture - Loboguerrero Rodriguez, Ana María; Hansen, James; Baethgen, Walter E.; Martínez Barón, Deissy (2017)
One of the main challenges of climate-smart agriculture (CSA) is finding ways to promote the adoption at scale (Editor’s note: 'scaling', 'at scale' or 'to scale' are used throughout this article to mean ‘scaling-out’) of CSA practices and technologies. Climate services and insurance can constitute a tool to scale CSA by providing an enabling environment that can support the adoption of CSA practices while protecting against the impacts of climate extremes. By using a definition of climate services which includes the production, translation, transfer, and use of climate knowledge and information in climate-informed decision-making and climatesmart policy and planning, this paper aims to discuss how climate services and insurance can bring CSA to scale. Three case studies are presented. It is recognised that understanding the knowledge networks through which information flows, and affects the use of climate information, is critical for promoting CSA at scale.